Hydro-biogeochemical modeling of the early-stage outbreak of green tide (Ulva prolifera) driven by land-based nutrient loads in the Jiangsu coast. (April 2020) - Chen, Yanan; Song, Dehai; Li, Keqiang; Gu, Linan; Wei, Aihong; Wang, Xiulin
Abstract: The outbreak of a large-scale green tide ( Ulva prolifera ) will have a serious impact on marine environment, ecological functions, landscape, and coastal social economy. Eutrophication is generally considered to be the most important driving factor of this phenomenon. It is difficult to obtain the pressure-impact relationship between land-based loading and green tides by only surveying or monitoring, whereas modeling can perform this task easily. In this study, therefore, a hydro-biogeochemical model was established and verified by the measured hydrodynamic and water quality variables. In the initial outbreak area of Jiangsu coast, China, we studied the relationship between U. prolifera bloom and the driving factors of nutrient loads and structures by modeling different scenarios of land source inputs. It was found that the ratio of nitrogen to phosphorus could be affected significantly, which triggered the bloom of U. prolifera . When the land-based input doubled or halved, the dissolved inorganic nitrogen concentration increased 20.6% or decreased 9.5%, respectively, which might result in 14.5% increase or 46.3% decrease in the green tide, respectively. It was also found that the nutrient distribution and structure was affected by the land-based load, which caused the outbreak of U. prolifera . Moreover, the total nutrient load must be controlled to prevent the outbreak of green tide in the Jiangsu coast.